APLIKASI PUPUK ORGANIK DAN BAKTERI PELARUT FOSFAT UNTUK MENINGKATKAN PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS MANIS (Zea mays saccaharta sturt L.) - Dick Dick Maulana; Lilis Irmawatie (PUCUK : Jurnal Ilmu Tanaman, 2022)
The use of organic matters on sweet corn cultivation is focused to decrease the utilization of chemical substances for minimizing environmental degradation. An experiment was conducted at Ujung Berung Indah Residence, Ujung Berung Districts, Bandung City (± 780 m asl.) from April to July 2020. The Aims of this research were to determine the suitable and effective inoculant to increase the growth of sweet corn plants. The sweet corn variety used was Bonanza F1 and the PSB inoculant that used was Bacillus Laterosporus. The organic fertilizers were compost, chicken and cow dung, and phosphate solubilizing bacteria (PSB), as a biofertilizer. A randomized block design with three replications was utilized in this experiment. The treatments consisted of without organic fertilizers or PSB (control) (K), inoculation of PSB (P1), application of compost (P2), (4) application of chicken and cow dung (P3), and application of the chemical fertilizer (NPK) (P4). The results showed that the application of organic fertilizers and PSB increased the growth of sweet corn plants after harvesting. The inoculation of PSB resulted in highest plant height compared to control and the highest sweet corn yield compared to the control treatment, and even it was higher than the yield caused by the application of the chemical fertilizer.